Recipe Recommendation With Hierarchical Graph Attention Network - Tian, Yijun; Zhang, Chuxu; Metoyer, Ronald; Chawla, Nitesh V. (Frontiers in Big Data, 2022)
Recipe recommendation systems play an important role in helping people find recipes that of their interest and fit their eating habit. Unlike what has been developed for recommending recipes using content-based or collaborative filtering approaches, the relational information among users, recipes, and food items is less explored. In this paper, we leverage the relational information into recipe recommendation and propose a graph learning approach to solve it. In particular, we propose HGAT, a novel hierarchical graph attention network for recipe recommendation. The proposed model can capture user history behavior, recipe content, and relational information through several neural network modules, including type-specific transformation, node-level attention, and relation-level attention. We further introduce a ranking-based objective function to optimize the model. Thorough experiments demonstrate that HGAT outperforms numerous baseline methods.